![1 + {tan}^{2} \beta + 1 + \frac{1}{ {tan}^{2} \beta } = \frac{1}{ {sin}^{2} \beta - {sin}^{4 \beta } } 1 + {tan}^{2} \beta + 1 + \frac{1}{ {tan}^{2} \beta } = \frac{1}{ {sin}^{2} \beta - {sin}^{4 \beta } }](https://tex.z-dn.net/?f=1+%2B+++%7Btan%7D%5E%7B2%7D++%5Cbeta+%2B+1+%2B++%5Cfrac%7B1%7D%7B+%7Btan%7D%5E%7B2%7D+%5Cbeta++%7D++%3D++%5Cfrac%7B1%7D%7B+%7Bsin%7D%5E%7B2%7D+%5Cbeta+++-++%7Bsin%7D%5E%7B4+%5Cbeta+%7D+%7D+)
plz answer this fast......
Answers
Answer:
Note: I am avoiding to write β. Instead I will be answering in terms of A.
L.H.S = 1+tan²A+1+1/tan²A
= 1 +sin²A/cos²A +1+cos²A/sin²A
= cos²A+sinA²/cos²A + sin²A+cos²A/sin²A
= 1/cos²A + 1/sin²A ⇒⇒⇒⇒⇒⇒ (∵ cos²A+sinA=1)
= sin²A/sin²A*cos²A + cos²A/sin²A*cos²A
= sin²A+cos²A/sin²A*cos²A
= 1/sin²A*cos²A ⇒⇒⇒⇒⇒⇒⇒ (∵ cos²A+sinA=1)
= 1/sin²A*(1-sin²A)⇒⇒⇒⇒⇒⇒ (∵ cos²A = 1-sin²A)
= 1/sin²A- = R.H.S
Hope you liked it........
Yours truly,
Shrest Kumar
Answer:
Step-by-step explanation:
LHS RHS
this is in the form of ( a + b ) ^2 1 / sin^2 [ 1 - sin^2 x ]
= ( tan x + 1 /tan x ) ^ 2 = 1 / sin^2x*cos^2x
= tan ^2 x + 1 / tan x = sec ^4 x / tan^2x = cosec^2 x * sec ^2x
= cosec^2 x * sec ^2x